Elmo's day - Snyder, Margaret; Kwiat, Ernie (Pleasantville, New York : Reader's Digest Children's Books, 2005)
"Elmo wants to share his day with you! There's so much to do and learn. While reading this story, kids will find five different wheel activities where they can match weather, clothing, colors, shapes, patterns, and animal sounds."--Cover.
At head of title: 123 Sesame Street
On board pages.
Keywords: Children's stories; Toy and movable books -- Specimens